Robust shell scripting : mastering portable and robust scripting with the POSIX Shell - Robbins, Arnold (O'Reilly, 2017)
"Designed for developers and system administrators with basic UNIX or Linux skills, this course gives you the fundamentals and then moves you beyond them, teaching you how to write production-level scripts with the POSIX shell."--Resource description page.